Meta-Analisis Pengaruh Model Pembelajaran Terintegrasi STEM terhadap Literasi Sains Peserta Didik dalam Pembelajaran IPA di Indonesia - I Kadek Arisujarnata; I Wayan Redhana; I Nyoman Tika (Postgraduate, University of Mataram, 2025)
In the 21st-century education era, scientific literacy has emerged as a crucial competency for addressing global challenges. The integrated STEM (Science, Technology, Engineering, and Mathematics) instructional approach is considered a promising strategy for enhancing students’ mastery of scientific literacy through interdisciplinary integration. However, there remains inconsistency in findings regarding the effectiveness of various STEM models, particularly within the Indonesian educational context. This study aims to examine the effectiveness of integrated STEM learning models on students’ scientific literacy in Indonesia through a meta-analytic approach. A total of 10 peer-reviewed articles published between 2021 and 2025 were analyzed using the Comprehensive Meta-Analysis (CMA) software version 4. The results indicate that STEM-based learning demonstrates a high overall effect size of 0.995 (categorized as large, p < 0.001). Among the models examined, Project-Based Learning (PjBL) emerged as the most effective and consistent model, while Problem-Based Learning (PBL) exhibited a relatively smaller effect size. Other models, such as Blended Learning, Inquiry Learning, and RADEC, also showed very high effectiveness; however, these findings require further empirical validation through additional studies. Moderator analysis revealed significant differences across the models (Qb = 7.85; p = 0.005), suggesting that the type of instructional model moderates the effectiveness of the STEM approach. These findings support the development of more evidence-based and contextually relevant science teaching strategies tailored to the Indonesian educational landscape.